Trends in forensic microbiology: From classical methods to deep learning - Yuan, Huiya; Wang, Ziwei; Wang, Zhi; Zhang, Fuyuan; Guan, Dawei; Zhao, Rui (Frontiers in Microbiology, 2023)
Forensic microbiology has been widely used in the diagnosis of causes and manner of death, identification of individuals, detection of crime locations, and estimation of postmortem interval. However, the traditional method, microbial culture, has low efficiency, high consumption, and low degree of quantitative analysis. With the development of high-throughput sequencing technology, advanced bioinformatics, and fast-evolving artificial intelligence, numerous machine learning models, such as RF, SVM, ANN, DNN, regression, PLS, ANOSIM, and ANOVA, have been established with advancement of microbiome and metagenomic studies. Recently, deep learning models, including convolutional neural network (CNN) model and CNN-derived models, improve the accuracy of forensic prognosis using the object detection techniques in microorganism image analysis. This review summarized the application and development of forensic microbiology, as well as the research progress of machine learning (ML) and deep learning (DL) based on microbial genome sequencing and microbial images, and provided a future outlook on forensic microbiology.